2005
DOI: 10.1093/ps/84.1.137
|View full text |Cite
|
Sign up to set email alerts
|

Preharvest feed withdrawal affects liver lipid and liver color in broiler chickens

Abstract: An Iowa grain processor attempted to alter the typical 12-h preharvest fasting period by giving broilers cornstarch derivative pellets and water for 6 h followed by 6 h of no feed or water. After slaughter, plant food inspectors determined that livers from the treatment group were lighter in color than normal, and consequently a significant number of chicken carcasses were condemned for human consumption. The study reported herein was conducted to determine the effects of fasting or 3 feeding programs applied … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
48
4
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(59 citation statements)
references
References 20 publications
5
48
4
2
Order By: Relevance
“…Moreover, they observed the yellowish livers in cholesterol fed broilers and pinkish livers in birds fed the control diet (without cholesterol). In other consistent study, Trampel et al (2005) indicated the higher liver weight and lighter colour in broiler chickens fed high dietary lipids and the redder colour in liver with low cholesterol content.…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…Moreover, they observed the yellowish livers in cholesterol fed broilers and pinkish livers in birds fed the control diet (without cholesterol). In other consistent study, Trampel et al (2005) indicated the higher liver weight and lighter colour in broiler chickens fed high dietary lipids and the redder colour in liver with low cholesterol content.…”
Section: Discussionmentioning
confidence: 73%
“…Moreover, orthogonal contrasts were constructed in order to compare the mean response variables for thyme extract received birds vs control birds. Correlation coefficients between the thyme consumption and blood cholesterol, abdominal fat and liver weights, and liver colour were calculated by the CORR procedure of SAS (Trampel et al, 2005).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies (Fanatico et al 2007;Mikulski et al 2011;Chen et al 2013), suggested that outdoor access had a positive effect on L* values, producing darker meat. Trampel et al (2005) reported that lighter liver colours were associated with more total liver lipid. In contrast, we found that livers of CC were lighter in colour and contained lower fat.…”
Section: Discussionmentioning
confidence: 98%
“…피트 모스의 사용은 축사의 환경에 영향을 미칠 뿐만 아니라, 동 물의 행동에도 영향을 미쳤다. 바닥재로서 피트모스를 2주 동안 사용한 결과, 1∼2주령의 암탉이 깃털을 쪼는 행동의 빈도수가 대조구보다 낮아졌고, 땅을 쪼거나 긁는 행동의 빈도수는 대조구보다 증가하였다 (Dixon and Duncan, 2010 (Trampel et al, 2005)과 사료 내 색소 의 함량에 따라서 영향을 받는 것으로 알려져 있다 (Loetscher et al, 2013). 사료 내 피트모스 함량이 0.8% 이상의 처리구 는 사료섭취량이 감소한 반면, 사료 내 색소의 함량이 증가하 여 간의 명도와 노란 정도가 증가한 것으로 사료된다.…”
unclassified